The poetic witness and his use in interpreting the vocabulary of the Holy Quran: The interpretation of ibn Attia(d542H) as a model - Bennaired, Hadj (Journal of Human Sciences, 2022)
The research presented the place of language in the interpretations of Maghrebs and Andalusians; its role in guiding semantics and meaning; the most important instrument of understanding and elicism in their interpretations, as a reaction to the multiplicity of different doctrines and linguistic differences and interprtatations of the holy Quran text, while most of the Maghreb and Andalus believe in the Achaari’s doctrine, ant the poetic witness has been the most important feature of the linguistic interpretation of the holy Quran, and the identification of the meaning semantics of words through the poems of the Arabs, above all the explanation (Al-mouharer Al-wajiz) of Ibn Attia al-andalusi (d542h); which became the source of most of the interpretations that came after him, and therefore we chose him as the subject of this research, this research was dedicated to presenting the evidence semantics of the semantics and vocabulary of the first part of it in the introductions of the book and the interpretation of sourate fatiha and Al-baquara.